Do Electricity Consumption and International Trade Openness Boost Economic Growth in Sudan? Empirical Analysis from Bounds Test to Cointegration Approach - Elfaki, Khalid Eltayeb; Anwar, Nurul; Arintoko, Arintoko (International Journal of Energy Economics and Policy, 2020)
Electricity power plays a significant role as an engine factor in boosting economic growth, particularly in developing countries. This paper utilized the autoregressive distributed lag (ARDL) model to study the interrelationship among electricity consumption, international trade openness, and economic growth in Sudan data spanning 1975-2014. The cointegration test result confirms the presence of long run cointegration relationship among electricity consumption, international trade openness, and economic growth. The estimated results of the long run point out that electricity consumption and international trade openness showed a significant positive relationship relating to economic growth. The estimated error correction term coefficient is found to be significant at a 1% significance level with an expected sign. The findings of this paper suggest that Sudan’s economy takes advantage of promoting electricity production and more open international trade. Therefore, the policies that support and encourage electricity generation for effective uses are highly recommended. The engagement in international trade creates opportunities for Sudan’s economy to benefit from the comparative advantage in exporting some goods that have a comparative advantage in Sudan as well as to import modern technologies particularly, the machineries and equipment relating to agriculture and industrial sectors recently to improve economic growth. Keywords: economic growth, trade openness, electricity consumption, ARDL, Sudan. JEL Classifications: F43, F16, L94 DOI: https://doi.org/10.32479/ijeep.9374